(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the life and creative work of Islom Shoir Nazar ogli, a representative of the Narpay epic school. It analyzes the plot of the epic "Orzigul", performed by him, and its significance in the artistic legacy of the bakhshi tradition.